Improving the Method of Cultivating Kk-60 Sunflower Elite Seeds under Aral Sea Conditions - Bakhytjan Uzakbaevich, Aytjanov; Uzakbay Eshanovich, Aytjanov; Raoaj Sarsenbaevich, Seytbaev (International Journal of Psychosocial Rehabilitation, 2020)
In this article, it will be explained that the sunflower, created in the conditions of the arid higher climatic conditions, is based on the seed scheme aimed at improving the quality of kk-60 sort; the assessment by generations is taken from mutual pollination among the most typical (and good) biotypes (in varieties) in the nursery, that is, on the basis of the